Beyond the surface: delving into plant signaling during flooding stress - Teoh, Ee Yang; Mohd Amnan, Muhammad Asyraf; Mohd Noor, Siti Nurfadhlina; Hamdan, Mohd Fadhli (Springer Science and Business Media LLC, 2024)
Flooding is a critical environmental challenge that affects plant growth and development, and its frequency and severity are expected to increase with climate change. Plants have evolved diverse acclimation responses to survive under unfavorable conditions. Some plants adopt either escape or quiescence strategies when submerged. In an escape strategy, plants elongate their internodes to maintain essential gas exchange, whereas in a quiescent strategy, they rely on carbohydrate reserves to sustain vital metabolic processes during submergence. Ethylene is a key player in plant adaptation to flooding and modulates signaling and metabolic responses. Although significant progress has been made in unraveling the fundamental physiological and molecular mechanisms associated with ethylene-mediated plant responses to flooding stress, our knowledge in this field is still incomplete. Understanding how plants cope with unforeseen flood events is crucial for developing resilient crop varieties. This review provides recent discoveries and an overview of plant responses and tolerance mechanisms to flooding stress, encompassing cellular signaling and morphological adaptations. By examining these aspects, we aimed to catalyze innovative approaches for crop improvement to enhance flood resilience.